KOREOGRAFI SEBAGAI PENDIDIKAN APRESIASI SENI BAGI SISWA SMA NEGERI 3 BOYOLALI - Soemaryatmi Soemaryatmi (Institut Seni Indonesia Surakarta, 2016)
Choreography workshop as an education of art appreciation is held in SMAN 3 Boyolali in order that the students can get direct experience to do creative work through movement. For the reason, the participant is not limited at the students following any extracurricular activities but also others who are interested in the workshop. Choreography workshop is supposed to give a chance for students to do creativities and to get aesthetic experience through movement activities (dance). Besides that, this workshop is also hoped to produce a positive effect in the cultivation of art feeling, creative attitude, and development of motivation in appreciating arts. The method used in this choreography workshop is the method of assignation play. The method is used because of the minimal backgrounds of the students. It can be said that only three of the sixteen students have ever studied dance. The choreography worksgop in SMAN 3 aims to motivate the students in ordering movements (pose-pose) to be a short choreography as well as demonstrate it.Key words : workshop, choreography, education, art.